TECHNIQUE AND TECHOLOGY OF RARE-METAL ORES DESINTEGRATION AND GRAVITY-BASED BENEFICATION - Shpylovyi, K. L.; Shpylovyi, L. V.; Biletskyi, V. S.; Komarova, O. I. (Academic journal Industrial Machine Building Civil Engineering, 2017)
On the base of the analysis of centrifugal concentrators designs there has been justified the selection of apparatus for the rare-metal ores benefication. Process of pyrochlore ore grinding in mills of different types has been investigated and the expediency of use of impact-centrifugal action mills to ensure selectivity of minirals disclosure has been founded. Efficient technical and technological parameters of the centrifugal action mills have been justified on the base of active experimental method. The influence of disintegration metheds on technologival indication of rare-metal ore benefication of Mazurovske deposits in centrifugal Nelson concentrator has been analyzed.
Keywords: centrifugal concentrator; ore preparation; gravity-based beneficiation in centrifugal field; disintegration; a mill of impact-centrifugal action type